Enhancing the physical and tribological characteristics of modified jatropha oil via the incorporation of hybrid nanoparticle additives - Ainaa, M. Sabri; Norfazillah, Talib; Amiril Sahab, Abdul Sani; Zubaidah, Zamri; Kamaruddin, Kamdani; Kunar, Sandip; Haslina, Abdullah (Malaysian Tribology Society (MYTRIBOS), 2024)
The objective of this study is to examine the physicochemical and tribological characteristics of Jatropha oil (MJO) that have been modified by incorporating 0.025 wt.% of activated carbon (AC) (MJOa), MJOa with hexagonal boron nitride (hBN)(MJOah) MJOa with titanium dioxide (TiO2) (MJOat), as well as MJOa with tungsten disulphide (WS2) (MJOaw). The physicochemical properties of the samples were assessed using kinematic viscosity and viscosity index measurements. The tribological performance of the samples was evaluated using the four-ball test. The findings indicate that MJOat exhibits favorable physicochemical characteristics, with a kinematic viscosity of 16.64 mm2/s at 40°C and 5.93 mm2/s at 100°C. The MJOat exhibited the highest viscosity index, measured at 360 followed by MJOah (339). In terms of tribological performance, it is observed that MJOah exhibits a commendable coefficient of friction (COF) value of 0.05465 and possesses the lowest surface roughness (Ra) of 0.23 μm. On the other hand, MJOah also demonstrates a smaller mean wear scar diameter (MWSD) of 595.3 μm and the lowest volume wear rate (2.964 × 10-7 mm3/s). SEM image of MJOah shows a smoother ball bearing worn surface compared to other samples. In general, utilizing MJO with hybrid additives demonstrates outstanding efficacy in enhancing both physicochemical and tribological characteristics.